2021
DOI: 10.7717/peerj.11052
|View full text |Cite
|
Sign up to set email alerts
|

Beyond gene ontology (GO): using biocuration approach to improve the gene nomenclature and functional annotation of rice S-domain kinase subfamily

Abstract: The S-domain subfamily of receptor-like kinases (SDRLKs) in plants is poorly characterized. Most members of this subfamily are currently assigned gene function based on the S-locus Receptor Kinase from Brassica that acts as the female determinant of self-incompatibility (SI). However, Brassica like SI mechanisms does not exist in most plants. Thus, automated Gene Ontology (GO) pipelines are not sufficient for functional annotation of SDRLK subfamily members and lead to erroneous association with the GO biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 68 publications
(135 reference statements)
0
20
0
Order By: Relevance
“…The phenotypic analysis indicated that the IRO2 overexpression lines germinated and grew better than the WT, while the IRO2-RNAi lines grew slower than the WT [ 74 ]. The D-mannose-binding lectin family protein/S-Domain receptor-like protein-11 (SDRLP-11) is characterized by Ser/Thr kinase domains and induced by salicylic acid [ 75 , 76 ]. Ubiquitin carboxyl-terminal hydrolase family 1/ubiquitin c-terminal hydrolase 5 (UCH5) is an uncharacterized protein.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic analysis indicated that the IRO2 overexpression lines germinated and grew better than the WT, while the IRO2-RNAi lines grew slower than the WT [ 74 ]. The D-mannose-binding lectin family protein/S-Domain receptor-like protein-11 (SDRLP-11) is characterized by Ser/Thr kinase domains and induced by salicylic acid [ 75 , 76 ]. Ubiquitin carboxyl-terminal hydrolase family 1/ubiquitin c-terminal hydrolase 5 (UCH5) is an uncharacterized protein.…”
Section: Discussionmentioning
confidence: 99%
“…In the qSUB6-1 region, Os06g0164900 was reported to have S-Domain receptor-like kinase-66 (SDRLK-66) that responds to chilling and submergence. Also, in the qSUB12-1 region, Os12g0130500 was reported to have S-Domain receptor like protein-6 (SDRLP-6) that responds to submergence (Mondal et al 2021;Naithani et al 2021). One of the detected QTLs overlapped with the reported qSUB12.1 for submergence tolerance.…”
Section: Discussionmentioning
confidence: 87%
“…One of the candidate genes for mannose content was LOC_Os09g02410 , an S ‐domain receptor‐like kinase (SDRLK; Table 1), which is originally found in self‐incompatibility responses in Brassica (Zou et al., 2015). Rice has 144 members of SDRLK with varieties of functions in biotic/abiotic stress responses and development (Chen et al., 2013; Fan et al., 2018; Naithani et al., 2021). Transgenic rice plants carrying anti‐sense for a member of SDRLK ( OsESG1 ) developed into fewer crown roots and shorter shoots at seedling stage compared with wild type (Pan et al., 2020).…”
Section: Discussionmentioning
confidence: 99%